2021
DOI: 10.3390/ma14226939
|View full text |Cite
|
Sign up to set email alerts
|

Combining Chromatographic, Rheological, and Mechanical Analysis to Study the Manufacturing Potential of Acrylic Blends into Polyacrylic Casts

Abstract: Polyacrylics have been considered for a broad range of material applications, including coatings, dental applications, and adhesives. In this experimental study, the casting potential of a group of (co)monomers belonging to the acrylic family has been explored to enable a more sustainable use of these polymer materials in the medical and veterinary science field. The individual contributions of each comonomer have been analyzed, the reaction conversion has been studied via gas chromatography (GC), the rheologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 100 publications
(144 reference statements)
0
14
0
Order By: Relevance
“…Recently, Reyes et al demonstrated the behavior of viscosity changes for MMA-based formulations undergoing polymerization. 36 The results of this study highlight the effect of the chemical formulation, shear rate, and temperature on the pot life of a polymerizing material. Once a viscosity value of 1000 mPa s was reached an assessment of the pot life became possible.…”
Section: Mma-based Resinsmentioning
confidence: 75%
See 3 more Smart Citations
“…Recently, Reyes et al demonstrated the behavior of viscosity changes for MMA-based formulations undergoing polymerization. 36 The results of this study highlight the effect of the chemical formulation, shear rate, and temperature on the pot life of a polymerizing material. Once a viscosity value of 1000 mPa s was reached an assessment of the pot life became possible.…”
Section: Mma-based Resinsmentioning
confidence: 75%
“…Recent rheological research has made clear that viscosity is not a static parameter that can be assessed without taking into account the local processing conditions. Likely one of the most important processing factors is the (varying) shear rate, which affects the way viscosity builds up in a casting system 36 . Therefore, it is worthwhile exploring the process condition variations that a casting resin undergoes as it is injected.…”
Section: Macroscopic Tools and Criteria For Casting Medium Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous more molecular-scale-driven research has shown that PMMA-based corrosion casting still needs to be adapted to better tune the pot life, the flow and filling performance and the durability and sustainability [ 32 , 35 , 36 , 37 , 40 , 41 ]. In this framework, the manufacturing of PMMA replicas is worthwhile to study both from the chemical-formulation-design and the polymer-processing-technique point of view with aims to deliver casts with more superior properties [ 42 ]. Chemical formulation design is at first sight the most interesting route for next-generation corrosion casting.…”
Section: Introductionmentioning
confidence: 99%